Análise do potencial das células-tronco mesenquimais de polpa de dente decíduo humano na regeneração óssea em crânio de coelhos - Belmonte, Gustavo Campos (2011)
The treatment of bone defects has been the subject of numerous studies in recent decades, especially in the cases of large dimensions, also called critical size defect. In the healing process of large lesions, the slower proliferation of osteoblasts may lead the connective tissue to form granulation tissue, filling the area with fibrous tissue occupying most of the defect site, preventing the action of specific cells in the bone regeneration. This study analyzed the results of regenerative procedures using stem cells from dental pulp of human deciduous teeth (CDLH1) in combination with autologous platelet-rich plasma (PRP) for the treatment of bone defects in rabbit calvaria. A total of 14 animals were used in the experiment in which bilateral bicortical bone defects of 10mm diameter in the skull were created. One of the defects of each animal was filled with CDLH1/PRP (test defect) and the other with only PRP (control defect). The results were evaluated 7 and 60 days post-surgery. The results showed that the CDLH1/PRP produced a higher percentage (84 + / -8%) of newly formed bone in 60 days compared with specimens from the PRP group (70 + / -10%), reinforcing the osteogenic potential of stem cells derived from the pulp of deciduous teeth in the treatment of bone defects.